2018
DOI: 10.1007/s10719-018-9837-4
|View full text |Cite
|
Sign up to set email alerts
|

Keeping it trim: roles of neuraminidases in CNS function

Abstract: The sialylated glyconjugates (SGC) are found in abundance on the surface of brain cells, where they form a dense array of glycans mediating cell/cell and cell/protein recognition in numerous physiological and pathological processes. Metabolic genetic blocks in processing and catabolism of SGC result in development of severe storage disorders, dominated by CNS involvement including marked neuroinflammation and neurodegeneration, the pathophysiological mechanisms of which are still discussed. SGC patterns in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 101 publications
1
45
0
1
Order By: Relevance
“…We speculate that the neuron uses the sialylation state of different populations of membrane biomolecules, such as gangliosides, ion channels, and receptors, to finely modulate their electrophysiological behavior. This is consistent with the presence of multiple endogenous neuraminidase enzymes in the brain that possess different substrate specificity and are actively regulated in response to electrophysiological activity (Pshezhetsky and Ashmarina, 2018). Prior studies demonstrating that blocking endogenous neuraminidase activity affects network spiking properties further support this hypothesis (Isaeva et al, 2010).…”
Section: Discussionsupporting
confidence: 73%
“…We speculate that the neuron uses the sialylation state of different populations of membrane biomolecules, such as gangliosides, ion channels, and receptors, to finely modulate their electrophysiological behavior. This is consistent with the presence of multiple endogenous neuraminidase enzymes in the brain that possess different substrate specificity and are actively regulated in response to electrophysiological activity (Pshezhetsky and Ashmarina, 2018). Prior studies demonstrating that blocking endogenous neuraminidase activity affects network spiking properties further support this hypothesis (Isaeva et al, 2010).…”
Section: Discussionsupporting
confidence: 73%
“…Sialidase 3 (a membrane sialidase, also called N-acetyl-alpha-neuraminidase 3; NEU3) is encoded by the NEU3 gene and localized in the plasma membrane, while sialidase 4 (N-acetyl-alpha-neuraminidase 4; NEU4) is encoded by the NEU4 gene and displays on internal membranes. In the mouse brain, NEU1, NEU3 and NEU4 show similar expression patterns [ 69 , 70 ]. Moreover, these sialidases are active against different but overlapping sialylated glycoconjugates.…”
Section: Sialic Acids (Sias): Structure Diversity Biosynthesis Rmentioning
confidence: 99%
“…Sialic acid, as a class amino sugar, is usually located at the end of the sugar chain on the cell membrane. In the CNS, neuraminic acid mainly combines with sphingolipid to form ganglioside, which plays an important role in neurogenesis, synaptic plasticity, and nerve impulse transmission [46]. Compared with CG, the concentration of neuraminic acid was significantly increased in 6 brain regions after administration, especially in the cortex, hypothalamus, and oblongata (Figure 4), which suggested that EP markedly changed the amino sugar metabolism in the three regions.…”
Section: Amino Sugar Metabolismmentioning
confidence: 95%